Diurnal variation of precipitation over Himalayan region - Singh, Prasamsa; Furuzawa, F. A.; Nakamura, Kenji (My University, 2004)
The diurnal cycle of precipitation is one of the strongest components of variablility of precipitation. The study was focused on diurnal variation of precipitation normal to the Himalayan range using the Tropical Rain Measuring Mission (TRMM) Precipitation Radar (PR), instantaneous data over the period 1998-2002. Gtopo30 (Digital elevation map (DEM) with spatial resolution 30 was used for study topographic height. During June, July and August late night/morning rainfall is dominated over the slope and foothill of mountains, while afternoon/evening rainfall dominated over Tibetan Plateau and Deccan Plateau. Foothill of the mountain and Deccan Plateau is characterized by convective rainfall where as Tibetan plateau and slope of the mountain is characterized by stratiform rainfall. It is also noticed that rainfall shifts southward during morning period.
Diurnal variation of precipitation over Himalayan region
Presented on Sepember 27-October 1, 2004 at The International Conference on Hydrology of Mountain Environments in Berchtesgaden, Federal Republic of Germany.
Keywords: precipitation; Himalayas